Dyes Adsorption On Salak Peel Based Activated Carbon Optimization, Equilibrium, Kinetic And Thermodynamic Studies - Zaki, Nur Izzatul Akmal Mohd (2015)
The adsorption of malachite green (MG) and remazol brilliant blue R (RBBR) dyes onto salak peel activated carbon (SPAC) were investigated in a batch process. Salak peel undergoes physiochemical activation process which involves potassium hydroxide (KOH) impregnation and carbon dioxide (CO2) gasification. During the preparation of SPAC, the optimum preparation conditions were obtained from response surface methodology (RSM). The optimum conditions are activation temperature, activation time and KOH:char impregnation ratio (IR) with 792°C and 1 hours and 3:1 respectively, which has resulted in 81.74% MG removal, 63.97% RBBR removal and 32.45% SPAC yield. Optimized SPAC has high of surface area (968.32m2/g), pore volume (0.503 cm3/g) and fixed carbon content (79.3%). The pore of SPAC was mesoporous type with average pore diameter of 4.41 nm. The effect of initial dye concentration (100-500 mg/L), contact time (0–24 hours) and solution temperature (30-60oC) were also evaluated through. The obtained equilibrium data for both dyes were best fitted by Langmuir model. Meanwhile, the kinetics data were best represented by the pseudo second-order model for MG and pseudo-first-order model for RBBR. The adsorption process of MG and RBBR onto SPAC were endothermic in nature.